(untitled) (Research, Society and Development, 2022)
Malignant head and neck tumors comprise several types of cancer, including primarily squamous cell carcinoma and tumors of the nasal cavity, sinuses, salivary glands, pharynx, and larynx. HANC survival rates vary depending on the tumor site. Five-year survival rates range from 27.8% for hypopharyngeal cancer to 67.0% for salivary gland cancer. In this context, this article aimed to review the literature on the effects of radiotherapy on the oral conditions of cancer patients and to address oral management strategies for head and neck radiotherapy. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. The articles were collected from February to July 2022 and covered between the years 2015 to 2022. The results of this research reveal four main manifestations in the oral region from head and neck radiotherapy, namely xerostomia, oral mucositis, osteoradionecrosis and trismus. Considering the high incidences of PPC, it is extremely important that health professionals are familiar with the complications arising from cancer treatments.